Solar-Powered Filtration: An Investigation into Clean Water Treatment Performance - Firda, Herlina; Faisal, Rahman; Ruliana, F.; Jainal, Arifin; Agus, Wiramsya; M., Suprapto; Ice, Trianiza; Rendi, .; Ahmadil, Amin; Mujiburahman, .; Dwiretnosari, .; Yuli, Panca (INTI International University, 2025)
Untreated wastewater significantly threatens both environmental health and human well-being, highlighting the importance of effective water treatment worldwide. This study evaluates a solar-powered filtration system as a practical alternative, especially for areas with limited infrastructure. The system uses solar panels to drive a water pump and filtration unit, with Powdered Activated Carbon (PAC) and aluminum sulfate serving as the primary filtration materials. Tests were carried out on samples from rivers and wells. Laboratory analysis showed that, after treatment, river water contained Fe = 0.81 mg/L, Mn = 0.08 mg/L, and hardness = 106.8 mg/L, while well water contained Fe = 0.26 mg/L, Mn = 0.04 mg/L, and hardness = 53.4 mg/L. These results indicate a substantial reduction in contaminants, bringing water quality close to clean water standards. Overall, the solar-powered system presents an effective, renewable, and eco-friendly method for producing safe water in remote or infrastructure-limited regions.